DETERMINAN FEE AUDIT : STUDI KASUS PADA ENTITAS MIKRO, KECIL DAN MENENGAH DI PROVINSI BANTEN - Roza Mulyadi; Chandra Prasadhita (COMPETITIVE, 2020)
Audit fees are important in the process of auditing a financial statement. The main objective of this research is to empirically investigate the determinants that influence audit fees for EMKM sector companies such as company size, profitability, company risk, complexity, type of industry and the status of the Public Accounting Firm. Samples taken from this study were 34 EMKM companies in Banten Province. The data source used is primary data. Primary data obtained by distributing questionnaires to respondents. The results of this study indicate that company size and company risk have a significant relationship to audit fees, while company profitability, complexity, type of industry, and KAP status do not have a significant relationship.